Відповідь:
1)(b-6)/(b-3)-b/(3-b)=2
2)(6с+4)/(7-с)+(3с+25)/(с-7)=-3
3)(3а+1)^2/(24a-24)+(a+3)^2/(24-24a)=(a+1)/3
4)(36-8x)/(x-6)^2-(4x-x^2)/(6-x)^2=1
Пояснення:
1)(b-6)/(b-3)-b/(3-b)=(b-6)/(b-3)+b/(b-3)=(2b-6)/(b-3)=2(b-3)/(b-3)=2
2)(6с+4)/(7-с)+(3с+25)/(с-7)=(3с+25)/(с-7)-(6с+4)/(с-7)=(3с+25-6с-4)/(с-7)=(-3с+21)/(с-7)=
(-3(с-7))/(с-7)=-3
3)(3а+1)^2/(24a-24)+(a+3)^2/(24-24a)=(9a^2+6a+1)/(24a-24)-(a^2+6a+9)/(24a-24)
=(9a^2+6a+1-a^2-6a-9)/(24a-24)=(8a^2-8)/(24(a-1))=(a^2-1)/(3(a-1))=(a-1)(a+1)/(3(a-1))
=(a+1)/3
4)(36-8x)/(x-6)^2-(4x-x^2)/(6-x)^2=(36-8x)/(x-6)^2-(4x-x^2)/(x-6)^2=(36-8x-4x+x^2)/(x-6)^2=
(x^2-12x+36)/(x-6)^2=(x-6)^2/(x-6)^2=1
D(y)∈(-∞;∞)
y(-x)=-2/3x³-x²+4x+5 ни четная и ни нечетная
y`=2x²-2x-4=0
x²-x-2=0
x1+x2=1 U x1*x2=-2
x1=-1 U x2=2
+ _ +
(-1)(2)
возр max убыв min возр
ymax=y(-1)=-2/3-1+4+5=7 1/3
ymin=y(2)=16/3-4-8+5=10 1/3-12=-1 2/3
y``=4x-2=0
x=0,5
y(0,5)=1/12-1/4-2+5=2 2/6
(0,5;2 2/6)-точка перегиба
_ +
(0,5)
выпук вверх вогн вниз
Объяснение: